THE EFFECT OF CAPITAL ADEQUACY, OPERATIONAL EFFICIENCY, ASSET QUALITY, AND SHARIA SUPERVISORY BOARD PERFORMANCE ON THE FINANCIAL PERFORMANCE OF SHARIA COMMERCIAL BANKS REGISTERED WITH THE FINANCIAL SERVICES AUTHORITY IN THE PERIOD 2019-2023 - Raeynindha Dzulfia; Indra Setiawan (International Journal Management and Economic, 2026)
This inquiry endeavors to assess the influence on capital adequacy, operational efficiency, asset quality, and Sharia Supervisory Board performance on the financial performance of Sharia Commercial Banks listed by the Financial Services Authority in the period 2019-2023. This research is an empirical study grounded in a quantitative causal-associative approach. The population examined comprises Sharia Commercial Banks listed by the Financial Services Authority spanning 2019-2023. The analytical sample was determined utilizing a purposive sampling approach, yielding nine Sharia Commercial Banks and a total of 45 observational units. The assessment utilised archival data extracted from annual reports published on the respective banks’ official web portals. The data were analysed applying panel-based econometric analysis processed using Eviews version 13. The findings substantiate that, partially, the operational efficiency variable exihibits a negative and significant bearing on financial performance. Meanwhile, the capital adequacy, asset quality, and Sharia Supervisory Board performance variables are not significantly associated with financial performance. These findings substantiate that the stability of financial performance in Sharia Commercial Banks is largely driven by the banks’ ability to maintain operational efficiency.